Unlocking the Full Value of Data – Mission (Im)Possible? - Petrošiūtė, Eglė; Sabanskaitė, Justė (Vilnius University Open Series, 2024)
The article provides insights into the growing popularity of new technologies and the amount of data that is being generated worldwide. Therefore, legislators are obligated to issue laws that are up to date. Hence, this article analyses the new proposed legislation in the European Union that ensures the possibility for individuals and businesses to gain access and exert control over data and share it with third parties. The authors of this paper conclude that the opportunity of freely sharing generated data is worthwhile, however, the drawbacks, such as concerns about privacy, potential discrimination and biases, as well as lack of infrastructure and personal data protection, should also be considered.
Keywords: Data Act; GDPR; data; sensors; Internet of Things